Pengaruh Literasi Digital Terhadap Kinerja Debitur Pembiayaan Ultra Mikro Melalui Kemampuan Manajerial di Kabupaten Mamuju - Mohammad Ali Arifin; Daru Asih; Syahrinullah Syahrinullah (Al-Buhuts, 2026)
This study aims to examine the effect of digital literacy on the performance of Ultra-Micro Financing (UMi) debtors through managerial capability in Mamuju Regency. The research employed a quantitative method with a confirmatory survey approach. The sample consisted of 337 active UMi debtors in Mamuju Regency, selected using purposive sampling based on criteria of utilizing digital transactions and having received business assistance. Primary data were collected through structured questionnaires using a Likert scale and analyzed using PLS-SEM. The results indicate that digital literacy has a positive and significant effect on managerial capability, and also influences debtor performance both directly and indirectly through managerial capability. Debtors with higher levels of digital literacy demonstrate better abilities in business planning, financial management, marketing strategies, and decision-making, which contribute to improved business outcomes.The novelty of this study lies in highlighting the mediating role of managerial capability in strengthening the relationship between digital literacy and debtor performance within the context of ultra-micro financing, particularly in regions experiencing declining financing distribution.